(The Effects of Bromeline Extract of Pineapple as Bating Agent on The Vegatable Tanning of Rabbits Leather) - -, Prayitno; Mulyono, Agus; Setyawardani, Triana (Balai Besar Industri Agro, 2004)
The effects of bromeline extract of pineapple as batting agent on the vegetable tanning of rabbits leather have been investigated the concentration treatment for bromeline extract were 1%, 1.5% and 2% of bloten weight meanwhile batting process time employed were 30,45,and 60 minutes the design experimental method employed in this research was completely randomaized design (CDR) factorial 3x3 with three reptitions .the testing parameters observed were sewn quality and tearn resistance the showsd thatsewn quality was affected significantly for batting time (p>0.05)but tearn resistance was not significantly influenced ,meanwhile the bromeline extract dosage affected unsignificanttly (p>0.05) on sewn quality as well as on tearn resisntace.by concentration of extract bromeline 1%; 1.5%;and 2% thesewn quality and tearn resistance met indonesian national standard (SNI)of leather glove at 45 and 60 minutes of batting time respectively.Â Â